Calculation and Design of Transmission System in the Design of Empty Palm Oil Fruit Bunches Chopper Machine with a Capacity of 100 Kg / Hour - Dimitra Meidina Kusnadi; Mashuri; Muhammad Dimasromanda Hidayatullah; Muhammad Lukman Hakim; Suhariyanto (IPTEK The Journal of Engineering, 2023)
The waste of empty palm fruit bunches (EFB) as compost material and as fiber material needs to go through a decomposition and chopping process to simplify the processing process. The empty palm fruit bunches (EFB) chopping machine has now been developed in various regions using various types of transmission, propulsion, and also various models. The design of chopping machines is also increasingly diverse in line with the increasing market demand for processed products from empty palm fruit bunches (EFB). Based on these conditions, an appropriate transmission system is needed to lighten the workload of the machine, increase production yields, and save production costs. From the results of the research, it was found that the empty palm fruit bunches chopping machine with a total capacity of 100 kg / hour was tested. The machine is driven by an electric motor with a power of 4 kW and a rotational speed of 1440 rpm, which is transmitted using a pulley and belt open drive transmission system. The power from the machine is transmitted to the cutting section to chop the empty palm fruit bunches well.